2015
DOI: 10.1155/2015/412501
|View full text |Cite
|
Sign up to set email alerts
|

An Antioxidant Dietary Supplement Improves Brain-Derived Neurotrophic Factor Levels in Serum of Aged Dogs: Preliminary Results

Abstract: Biological aging is characterized by a progressive accumulation of oxidative damage and decreased endogenous antioxidant defense mechanisms. The production of oxidants by normal metabolism damages proteins, lipids, and nucleotides, which may contribute to cognitive impairment. In this study 36 dogs were randomly divided into four groups and fed croquettes of different compositions for 6 months. We monitored derivatives of reactive oxygen metabolites (dROMs) and biological antioxidant potential (BAP) levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…While the clinical improvement was supported by the enhancements in the serological data, no neurological mechanism of action was established in the study. Additionally, animal studies and at least one human study have shown that many of the nutrients in APMC, including polysaccharides, antioxidants, resveratrol, and omega-3 fatty acids, have individual benefits on cognition and memory [17][18][19][20][21] and can increase BDNF levels [22][23][24][25]. The sum of these findings suggests that long-term oral supplementation can modulate BDNF production in the brain and can also explain the memory improvements demonstrated in our prior studies.…”
Section: Journal Of Clinical and Translational Researchsupporting
confidence: 55%
“…While the clinical improvement was supported by the enhancements in the serological data, no neurological mechanism of action was established in the study. Additionally, animal studies and at least one human study have shown that many of the nutrients in APMC, including polysaccharides, antioxidants, resveratrol, and omega-3 fatty acids, have individual benefits on cognition and memory [17][18][19][20][21] and can increase BDNF levels [22][23][24][25]. The sum of these findings suggests that long-term oral supplementation can modulate BDNF production in the brain and can also explain the memory improvements demonstrated in our prior studies.…”
Section: Journal Of Clinical and Translational Researchsupporting
confidence: 55%
“…In dogs and cats, the availability of functional food for weight loss, against behavioral disorders, and chronic inflammation, has been discussed by many researchers ( 23 – 28 ), and the role of supplements with anti-oxidant and anti-inflamatory effect has been reported ( 29 , 30 ) There are many reports discussing anti-obesity effects of anti-oxidant polyphenols such as isoflavone ( 31 33 ) anthocyanin ( 34 36 ), catechin ( 37 39 ), and quercetin ( 40 42 ). Especially, quercetin glycoside is a well-known compound since its metabolic pathway route in human intestine is clarified ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some scientific evidence has pointed out the efficacy of selected ingredients, as part of a commercially available diet, in relieving inflammatory conditions in pets by means of an immune modulatory and antioxidant activity [49][50][51][52][53][54][55][56][57].…”
Section: Pet Diets and Animal Well-beingmentioning
confidence: 99%
“…In some cases, substances endowed with anti-inflammatory as well as immune-modulatory activity can drastically influence the clinical outcome of lethal pathologies, that is, Leishmania [63]. In other cases, the selection of substances with a remarkable antioxidant activity also acquires a pivotal role in other clinical conditions, which are not strictly related to adverse food reactions, that is, cognitive impairment, as a consequence of aging or pathologies such as Alzheimer's and Parkinson's disease [52,64,65].…”
Section: Pet Diets and Animal Well-beingmentioning
confidence: 99%
See 1 more Smart Citation